VLTI/AMBER spectro-interferometric imaging of VX Sagittarii's inhomogenous outer atmosphere - Chiavassa, Andrea; Lacour, S.; Millour, F.; Driebe, T.; Wittkowski, M.; Plez, B.; Thiébaut, E.; Josselin, E.; Freytag, B.; Scholz, Michael; Haubois, X. (Astronomy and astrophysics, 2010)
Aims. We aim to explore the photosphere of the very cool late-type star VX Sgr and in particular the characterization of molecular layers above the continuum forming photosphere. Methods. We obtained interferometric observations with the VLTI/AMBER interferometer using the fringe tracker FINITO in the spectral domain 1.45-2.50 μm with a spectral resolution of and baselines ranging from 15 to 88 m. We performed independent image reconstruction for different wavelength bins and fit the interferometric data with a geometrical toy model. We also compared the data to 1D dynamical models of Miras atmosphere and to 3D hydrodynamical simulations of red supergiant (RSG) and asymptotic giant branch (AGB) stars. Results. Reconstructed images and visibilities show a strong wavelength dependence. The H-band images display two bright spots whose positions are confirmed by the geometrical toy model. The inhomogeneities are qualitatively predicted by 3D simulations. At μm and in the region μm, the photosphere appears extended and the radius is larger than in the H band. In this spectral region, the geometrical toy model locates a third bright spot outside the photosphere that can be a feature of the molecular layers. The wavelength dependence of the visibility can be qualitatively explained by 1D dynamical models of Mira atmospheres. The best-fitting photospheric models show a good match with the observed visibilities and give a photospheric diameter of ± 0.50 mas. The H2O molecule seems to be the dominant absorber in the molecular layers. Conclusions. We show that the atmosphere of VX Sgr seems to resemble Mira/AGB star model atmospheres more closely than do RSG model atmospheres. In particular, we see molecular (water) layers that are typical of Mira stars.
Gesehen am 09.03.2023